SNACK BAR TINGGI SERAT BERBASIS TEPUNG AMPAS TAHU (OKARA) DAN TEPUNG UBI UNGU - Nuri Rachmayani; Winiati P. Rahayu; Didah Nur Faridah; Elvira Syamsir (Jurnal Teknologi dan Industri Pangan, 2017)
Unbalanced dietary consumption, lack of dietary fiber intake and low physical activity could lead to excessive nutrients resulting in obesity. This research aims to create high-fiber snack food in the form of snack bar made from pulp of tofu flour (okara), purple sweet potato flour, and cornstarch. The experimental design was a complete factorial randomized design with two variables and two replications. Two variables tested were the ratio between purple sweet potato flour and cornstarch of 1:1 and 1:2 (w/w), and the addition okara of 20, 25, and 30%. As a control, a snack bar was made from wheat flour. The analysis performed include sensory and physicochemical analysis. The recommended high-fiber healthy snack bar was the snack bar made from 20% okara, with a ratio of purple sweet potato flour to cornstarch of 1:2 (w/w). This snack bar had a sensory score of 4.31 on the overall attribute which means neutral. The anthocyanin level of the cookies was 1.97 mg/100 g (db) and dietary fiber level was 13.87% (db), therefore they can be categorized as high fiber okara food according to the head of BPOM regulation number HK 03.1.23.11.11.09909 year 2011.